Transformasi Nilai Kemanusiaan di Era Digital: Tinjauan Humaniora terhadap Perubahan Pola Interaksi Sosial - Ahmad Nashiruddin Mubarak; Dewi Masitoh Ramdhaniyah; Muhammad Hafizh Sultoni Aziz (Nalar Bhinneka: Jurnal Humaniora, 2026)
The rapid development of digital technology has triggered fundamental changes in Indonesian society's social interaction patterns, including the transformation of human values that form the foundation of collective life. However, comprehensive humanities studies examining the value dimension of digital social interaction remain very limited. This study aims to analyze the transformation of human values in the digital era through a humanities perspective on changes in social interaction patterns. The method employed is a qualitative case study with phenomenological analysis. Data were collected through in-depth interviews, participant observation, and documentation across three different digital communities. Results show a shift in values from face-to-face dimensions toward digitally mediated dimensions, with new values such as limitless connectivity alongside the erosion of contextual empathy. It is concluded that the transformation of human values is ambivalent and requires reconstruction of digital ethics based on Indonesian local wisdom.